Determinación del momento óptimo del beneficio o saca en el engorde de ovinos de la raza pelibuey en el trópico de San Martín - Tong Hidalgo, Iris Tatiana (2016)
The quality of the soils and its uneven physiography that determines its good drainage, as well as the weather, have made the hair ovine prosper and spread in the region. San Martin has the highest population of “Pelibuey” ovine (25 000 head), in comparison to other rainforest areas. Nevertheless, the ovine breeding isn’t an attractive activity yet, due to the low demand in the market, caused by the lack of awareness of people about the consumption of the meat. There is also a prejudice, that rejects it due to its smell and taste (“aftertaste”), and the lack of technology that improves the productivity, these have determined that it is an activity with low profitability. It is important to revert this situation looking for a practical alternative, as the “FATTENING OF YOUNG OVINE”, for the production of meat, activity that will also allow to mobilize the internal market of the ovine breeding, increasing its consumption and demand, improving their profitability, and thus turning it into an important agriculture and livestock activity that would benefit the rural producer, increasing his income; and the rural and urban settlers, who would have another source of protein. This document was made with the aim of evaluating, in a 60-day period, five feeding programs to fatten young ovine: Free grazing and night confinement (T0), Stabling with grass + rice bran (T1), Stabling with grass + chopped leguminous (T2), Stabling with balanced food (T3), and Stabling with grass + balanced food (T4). The obtained results report better productive behaviors for the treatment T0, followed by the treatment T3, after treatment T2, and finally T1, so we can conclude that the fattening of ovine is more efficient when the grazing is carried out